LONG TERM FOLLOW-UP ON EFFECTIVENESS AND SAFETY OF ETANERCEPT IN JUVENILE IDIOPATHIC ARTHRITIS WITHOUT SYSTEMIC MANIFESTATIONS - A. A. Baranov; E. I. Alexeeva; T. M. Bzarova; S. I. Valieva; K. B. Isaeva; E. G. Chistyakova; A. M. Chomakhidze; R. V. Denisova; T. V. Sleptsova; A. N. Fetisova; O. L. Lomakina (Вопросы современной педиатрии, 2015)
Treatment of juvenile idiopathic arthritis (JIA) is one of the most complex and urgent problems of rheumatology. Objective: We undertook a study to evaluate the effectiveness and safety of long-term therapy with etanercept in patients with JIA without systemic manifestations. Methods and patients: Patients in the study were divided into 2 groups. Patients of the main group (n = 197) received etanercept, the comparison group (n = 200) - methotrexate. The effectiveness was assessed by the American College of Rheumatology (ACR) criteria and Wallace's criteria for clinical remission (CR) and the 4-year JADAS71 index. Results: We included 397 patients with JIA. In 6 months and 12 months a remission of articular syndrome was detected in 72 and 53 patients respectively; 83% and 65% of patients receiving etanercert and methotrexate, respectively. Laboratory indicators of disease activity corresponded with reference values in 91 and 48% in a period of 6 months, in 12 months - in 94 and 68% of patients. According to the results of Childhood Health Assessment Questionnaire (CHAQ) functional activity fully recovered in 65 and 79%; 30 and 58% of children in a period of 6 and 12 months of follow-up. Within 1 month improvement according to ACR pedi criteria 30/50/70 was achieved in 79/62/34% of patients treated by genetically engineered biological agents. After 6 months AKRpedi criteria 30/50/70 was achieved in 97/96/89% and 63/57/47% against the background of therapy with etanercept and methotrexate, respectively. Etanercept induced inactive stage of the disease / remission [6 (4, 9) and 12 (6, 18) months; p <0,0001, respectively] in significantly shorter time than methotrexate. Within 6 and 12 months of follow up inactive stage of the disease / remission was reported in 30 and 49% of patients treated with inhibitor etanercept, and 9 and 38% of patients receiving methotrexate. Disease activity index JADAS71 in children treated with etanercept was significantly lower than in patients treated with methotrexate for 1 year. Conclusion: Etanercept has a significantly faster and more pronounced anti-inflammatory effect than the classic immunosuppressant methotrexate.